2000
DOI: 10.1152/ajpendo.2000.279.2.e235
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia compensates for infection-induced impairment in net hepatic glucose uptake during TPN

Abstract: In animals receiving total parenteral nutrition (TPN), infection impairs net hepatic glucose uptake (NHGU) by 40% and induces mild hyperinsulinemia. In the normal animal, the majority of the glucose taken up by the liver is diverted to lactate, but in the infected state, lactate release is curtailed. Because of the hyperinsulinemia and reduced NHGU, more glucose is utilized by peripheral tissues. Our aims were to determine the role of infection-induced hyperinsulinemia in 1) limiting the fall in NHGU and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Net glycogen accumulation attributed to fructose was calculated as the increment in [ 14 C]glycogen synthetic rate (difference between fructoseinfused group and corresponding saline-infused group) multiplied by the fraction of time of fructose infusion (total min/180 min). Analogous to glycogen accumulation, hepatic 14 C-labeled lipid deposition was calculated as total radioactivity divided by inflowing [ 14 and sham ϩ saline (ShamϩS) groups have been presented previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…Net glycogen accumulation attributed to fructose was calculated as the increment in [ 14 C]glycogen synthetic rate (difference between fructoseinfused group and corresponding saline-infused group) multiplied by the fraction of time of fructose infusion (total min/180 min). Analogous to glycogen accumulation, hepatic 14 C-labeled lipid deposition was calculated as total radioactivity divided by inflowing [ 14 and sham ϩ saline (ShamϩS) groups have been presented previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…A laparotomy was performed on healthy dogs under general anesthesia, as described previously (8). During the laparotomy, Silastic (Dow Corning, Midland, MI) catheters (0.04 in.…”
Section: Experimental Preparationmentioning
confidence: 99%
“…Previous studies by our laboratory and others have demonstrated using hyperinsulinemic-euglycemic clamps that lipopolysaccharide (LPS) induces insulin resistance (39). Skeletal muscle is a major site of insulin-stimulated glucose disposal and a major contributor to sepsis-induced insulin resistance (12,34,35). Alterations in muscle glucose disposal, the control of which is distributed between delivery of glucose to muscle, glucose transport in the myocyte, and subsequent metabolism within the myocyte, can contribute to insulin resistance in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%